The Relationship Between Family Support and Medication Adherence Among Employees with Hypertension in a Shipping Logistics Company - Andri Theja; Shirley Moningkey; Marshell Handoko (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Hypertension is a major global health issue and ranks second among diseases at a shipping logistics company in Surabaya. Medication adherence is vital for preventing complications, yet evidence on family support remains inconsistent. Objective: This study examined the association between family support and medication adherence in hypertensive employees. Methods: A cross-sectional design with 84 purposively sampled hypertensive employees undergoing treatment was used. Data were collected via structured questionnaires on demographics, the Perceived Social Support from Family Scale, and the Hill-Bone Compliance Scale. Bivariate analysis used the Chi-square test. A family support intervention was piloted on five lowest-support respondents and evaluated with a paired t-test. Results and Discussion: Most participants were male, aged >50 years, and held a bachelor's degree. The majority reported strong family support and moderate adherence. A significant relationship was found (p<0.05); strong support correlated with >8-fold higher adherence likelihood. The intervention significantly increased support scores (p<0.05). Conclusions: Family support significantly associates with better medication adherence among hypertensive employees. Preliminary evidence suggests structured interventions can effectively enhance perceived family support